2022
DOI: 10.21203/rs.3.rs-1836086/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Detection and Disease Monitoring of Hepatocellular Carcinoma Using Circulating Telomere DNA

Abstract: Early cancer detection requires high-performing biomarkers and effective tools to enable early intervention. Telomeres, located at the terminal of linear chromosomes, affect genome integrity and cell immortalization. At the very end of the telomere is a 3’ overhanging guanine-rich tail (G-tail) of which shortening is closely related to cell divisions. However, G-tail DNA cannot be detected with conventional sequencing technologies. Here we develop a high-preservation technology to quantify telomeres in circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, it is the first time to characterize the intimate relationship of TL and mtDNA-CN in patients with CVD. Specifically, higher levels of leu-TL and leu-mtDNA may indicate physiological condition or a compensation stage ( 11 ), while higher levels of cf-TL and cf-mtDNA may indicate pathological condition or a decompensation stage ( 50 , 53 ). Here, a mounting number of studies have been performed to provide evidence that TL and mtDNA are coordinately regulated ( 54 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, it is the first time to characterize the intimate relationship of TL and mtDNA-CN in patients with CVD. Specifically, higher levels of leu-TL and leu-mtDNA may indicate physiological condition or a compensation stage ( 11 ), while higher levels of cf-TL and cf-mtDNA may indicate pathological condition or a decompensation stage ( 50 , 53 ). Here, a mounting number of studies have been performed to provide evidence that TL and mtDNA are coordinately regulated ( 54 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that telomeres and mitochondria ( 79 ) from immune cells play critical roles in peripheral arterial disease ( 80 ) and heart failure ( 81 ), respectively. In contrast, while cf-TL and cf-mtDNA may indicate stages of decompensation ( 50 , 53 ). Therefore, both cf-TL and cf-mtDNA have been regarded as new biomarkers in cancer diagnosis and treatment ( 82 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…As telomeric G-tail DNA cannot be detected with conventional sequencing technologies, Zheng et al developed a high-preservation technology to quantify telomeres in cfDNA. They showed that short G-tail DNA was nearly 20-fold higher in HCC patients than controls and was strongly correlated with lower survival [ 142 ]. A study by North indicated that serum cf-telDNA was present in glioblastoma patients at nearly double the amount of the levels in the non-cancer control group.…”
Section: Applications Of Telomeric Dna In Cancer Assessmentmentioning
confidence: 99%